Dynamics of formation of during inhibition of steel by sulfanilamide in solutions of hydrochloric acid with different pH - Kurmakova, I.M.; Bondar, O.S.; Holub, I.V.; Коrolev O.O. (Physics and Chemistry of Solid State, 2021)
Experimentally proved by the method of polarization resistance formation of protective layers during inhibition steel corrosion by Sulfanilamide in aqueous solutions of hydrochloric acid with different pH. It is shown the difference due to the predominance of the protonated or unprotonated form of the molecule. It was found that at predominance of protonated forms of molecules (pH £2,4) formed dense protective films and predominance of unprotonated forms of molecules (pH ³2,4) are formed layers that do not inhibit diffusion processes. Sulfanilamide provides high and stable inhibition efficiency (<90%) in acid chloride solutions in case of formation protective layers consisting of protonated molecules what to consider when use it.